Bioprospecting bacterial and fungal volatiles for sustainable agriculture. (April 2015) - Kanchiswamy, Chidananda Nagamangala; Malnoy, Mickael; Maffei, Massimo E.
Highlights MVOCs exert significant effects on microbes and plants. MVOCs are produced both below and above ground and interfere with the rhizosphere and the atmosphere. We propose that MVOCs can be exploited as an ecofriendly and sustainable strategy for agricultural practices. MVOCs could replace the need for genetic modification, harmful pesticides, fungicides, and bactericides.